As novas configurações do Estado sob as influências do terceiro setor na contemporaneidade : um estudo sobre o papel do voluntariado no âmbito empresarial e escolar - Miranda, Aline Barbosa de (2008)
This research has the purpose to problematize the devices wich are direct related with the new configurations of the relations between the public and private spheres, through the process of restructure the state. For this, will be problematize the expansion of the "third sector" and the impacts of their actions, that are spread in our communities through the volunteer work. From the beginning we have to assumption that the actions of social responsibility promoted by the companies, through the voluntary work developed by their employees, has a systematically contribute to the super-exploitation of the work force, that increase the mechanisms of value added in the production, and strengthen the capital control on the workers, through coercive actions. The dialectical materialism historical is the epistemological matrix which is the guide of this research, because, throw of the dialectical materialism historical we can study and analyze the totally category reality investigated. It is also a vital reference for analysis of the relationship between capital and work throw the potential analytical that is the concept of value added. This research was done through a bibliographic, using tracking of data in classic and contemporary themes that were essential for this work; documentary research was guided, above off all, in the legislation that regulate the object of this research and field research, witch was done in two companies located in Uberlândia - MG. Through the analyses undertaken we were able to learn that the neoliberal policies allied to the process of globalization of capital and new methods of management staff of enterprises are resulting in the affirmation of new forms to control the worker, through manipulate and coercive policies. These policies are responsible for intensifying the working day of employees, increasing the mechanisms of extraction of the value added through projects of social responsibility and the untrue volunteer work, in addition this thing helped to consolidate a new role of the state, in which changes occur in the design and foundations of social action. Thus, the provision of social issues, which are historically the responsibility of the state, are assumed by the civil sphere of society. Another relevant figure makes reference to the consequences of the opening of business logic in the spaces through cultural and educational projects developed by companies, because the space of the school should has a completely different dynamic of the business logic ruled in social Darwinism, meritocratic. Thus, those who can do everything go on, the others are excluded. In this space, the momentum should prevail the training of human beings, characterized by the historic patience in the construction of the other.